FENOMENA MESJID JAMI DIDALAM PANTI ASUHAN DI KOTA PALANGKA RAYA - Norhadi, Muhammad (Institut Agama Islam Negeri (IAIN) Syekh Nurjati Cirebon, 2024)
ABSCTRACTThis research is motivated by the establishment of a mosque in the orphanage complex, as well as carrying out Friday prayers. while in the area there is already a grand mosque that establishes Friday prayers. In fact, according to the majority, two Fridays are not allowed in one area. Because there will be Fridays that are not accepted. Therefore, the author aims to reveal the background of the establishment of the mosque and the implementation of Friday prayers in the orphanage complex. . This research is a type of empirical sociological juridical research with a socio-legal approach. This research uses observation, interview, and documentation data collection techniques. Data analysis techniques use data reduction and drawing conclusions, and data validity with triangulation. The results of the study are the establishment of the mosque and the implementation of Friday prayers in the orphanage complex are motivated by As one of the means of Fundraising for Orphanages, Maintaining Order in the Implementation of Friday Worship, Maintaining Order in the Implementation of Friday Worship, and Ease of Monitoring and Programs for Foster Children.Keywords: Jami Mosque, Taadud al Jumuah, Phenomenon, Orphanage AbstrakPenelitian ini dilatar belakangi oleh berdirinya Mesjid didalam komplek panti Asuhan, sekaligus melaksanakan ibadah jumat. sementara di Kawasan tersebut telah ada mesjid jami yang mendirikan sholat jumat. Padahal menurut jumhur bahwa dalam satu daerah tidak dibolehkan dilaksanakan dua jumat. Karena akan ada jumat yang tidak diterima. Oleh karena itu, penulis bertujuan mengungkap latar belakang pendirian mesjid dan pelaksaan jumat didalam komplek panti Asuhan. . Penelitian ini adalah jenis penelitian empiris yuridis sosiologi dengan pendekatan sosio-legal. Penelitian ini menggunakan teknik pengumpulan data observasi, wawancara, dan dokumentasi. Teknik analisis data menggunakan reduksi data dan penarikan kesimpulan, serta validitas data dengan triangulasi. Hasil Penelitian adalah pendirian mesjid dan pelaksanaan sholat jumat didalam komplek panti asuhan dilatar belakangi oleh Sebagai salah satu Sarana Fundrising Panti Asuhan, Menjaga Ketertiban Pelaksanaan Ibadah Jumat, Menjaga Ketertiban Pelaksanaan Ibadah Jumat, dan Kemudahan Monitoring dan Program terhadap Anak Asuh.Kata kunci: Mesjid Jami ,Taadud al Jumuah , Fenomena , Panti Asuhan